Divide the sum of /3, −/5, − /15 by the difference of /7 and /5.
Answers
Answered by
1
Answer:
(((((((((√Answer))))))))))
Sum of 5/8 and -11/12 = 5/8 + (-11/12)
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14(∵ LCM of 7 and 13 = 14)
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14(∵ LCM of 7 and 13 = 14)= (6 – 5)/14 or (5 -6)/14 = 1/14 or -1/14
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14(∵ LCM of 7 and 13 = 14)= (6 – 5)/14 or (5 -6)/14 = 1/14 or -1/14Now divide -7/24 by 1/14 or -1/14
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14(∵ LCM of 7 and 13 = 14)= (6 – 5)/14 or (5 -6)/14 = 1/14 or -1/14Now divide -7/24 by 1/14 or -1/14= (-7/24/1/14) or (-7/24 × (-14/1)
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14(∵ LCM of 7 and 13 = 14)= (6 – 5)/14 or (5 -6)/14 = 1/14 or -1/14Now divide -7/24 by 1/14 or -1/14= (-7/24/1/14) or (-7/24 × (-14/1)= (-7/24) × 14/1 or -7/24 × -14/1
Sum of 5/8 and -11/12 = 5/8 + (-11/12)= 5/8 – 11/12= (5 × 3) – (11 × 2)= 5/8 – 11/12= [(5 × 3) – (11 × 2)]/24(∵ LCM of 8 and 12 = 24)= (15 – 22)/24 = -7/24Now, difference of 3/7 and 5/14= 3/7 – 5/14 or 5/14 – 3/7= [(3 × 2) – (5 × 1)]/14 or [5 – (3 × 2)]/14(∵ LCM of 7 and 13 = 14)= (6 – 5)/14 or (5 -6)/14 = 1/14 or -1/14Now divide -7/24 by 1/14 or -1/14= (-7/24/1/14) or (-7/24 × (-14/1)= (-7/24) × 14/1 or -7/24 × -14/1= -49/12 or 49/12 = -4. 1/12 or 4. 1/12
Similar questions